INTERNALISASI NILAI-NILAI TRISILAS WISDOM DALAM PEMBENTUKAN KARAKTER SISWA DI SEKOLAH - Lili Dianah, Lili Dianah; Slamet Nopharipaldi Rohman, Slamet Nopharipaldi Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the process of internalizing Trisilas Wisdom values ​​in character building for students in schools. Trisilas Wisdom, as a concept of wisdom encompassing moral, social, and spiritual values, is believed to have a strategic role in strengthening character education in elementary education settings. This study used a qualitative approach with descriptive methods. The research subjects included teachers, students, and principals who were selected purposively. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing, as well as data validity testing through source and technique triangulation. The results showed that internalization of Trisilas Wisdom values ​​was carried out through classroom learning activities, school cultural habits, and teacher role models. These values ​​were reflected in students' attitudes of discipline, responsibility, social concern, and religiosity. Supporting factors included teacher commitment, a conducive school environment, and integration of values ​​into the curriculum, while inhibiting factors included limited student understanding and lack of parental involvement. Thus, internalization of Trisilas Wisdom values ​​was proven to contribute positively to shaping students' character holistically.